An ethylene cross-bridged pentaazamacrocycle and its Cu2+ complex: constrained ligand topology and excellent kinetic stability. Issue 54 (8th June 2020) - Shircliff, Anthony D.; Burke, Benjamin P.; Davilla, Dustin J.; Burgess, Gwendolyn E.; Okorocha, Faith A.; Shrestha, Alina; Allbritton, Elisabeth M. A.; Nguyen, Phillip T.; Lamar, Rachael L.; Jones, Donald G.; Gorbet, Michael-Joseph; Allen, Michael B.; et al.
Abstract : Extending the benefits of ethylene cross-bridging to pentaazamacrocycles has been achieved and a transition metal complex prepared and structurally characterized. Abstract : Rigid and topologically constrained ethylene cross-bridged tetraazamacrocycles have been increasingly utilised for thirty years as they form remarkably stable transition metal complexes for catalysis, biomedical imaging, and inorganic drug molecule applications. Extending these benefits to pentaazamacrocycles has been achieved and a first transition metal complex prepared and structurally characterized.